The Impact of Nutritional Supplementation on Donor Kidneys During Oxygenated Ex Vivo Subnormothermic Preservation. Issue 10 (22nd September 2022) - Bhattacharjee, Rabindra N.; Jackson, Ashley; Ruthirakanthan, Aushanth; Juriasingani, Smriti; Levine, Max A.; Jiang, Larry; Patel, Ram; Richard-Mohamed, Mahms; Forrest, Sheryl; Ravichandran, Sevanthi; Sener, Alp; Luke, Patrick P.
Abstract : Background: Evidence suggests that nutritional supplementation during normothermic ex vivo perfusion improves organ preservation. However, it is unclear whether the same benefit is observed during room temperature (subnormothermic) oxygenated perfusion. In this study, we tested the impact of providing complete nutrition during subnormothermic perfusion on kidney outcomes. Methods: Porcine kidneys were recovered after 30 min of cross clamping the renal artery in situ to simulate warm ischemic injury. After flushing with preservation solution, paired kidneys were cannulated and randomly assigned to perfusion with either (1) hemoglobin-carrier hemoglobin-based oxygen carrier or (2) hemoglobin-based oxygen carrier + total parenteral nutrition (TPN) for 12 h at 22 °C. To mimic reperfusion injury, all kidneys were reperfused with whole blood for an additional 4 h at 37 °C. Kidney function and damage were assessed. Results: Kidneys preserved with or without TPN performed equally well, showing similar renal function postreperfusion. Histological findings indicated similar levels of damage from apoptosis staining and acute tubular necrosis scores in both groups. Additionally, markers of renal damage (KIM-1) and inflammation (IL-6; high-mobility group box 1) were similar between the groups. Conclusions: Unlike other studies using normothermic oxygenated perfusion platforms, nutritional supplementation does not appear to provide any additional benefit during ex vivo kidney preservation over 12 h evaluated by whole blood-based reperfusion method at subnormothermic temperature. Further study should include a kidney autotransplant model to assess the role of TPN in vivo.